The 4.2 ka Event and the End of the Maltese “Temple Period” - Groucutt, Huw S.; Carleton, W. Christopher; Fenech, Katrin; Gauci, Ritienne; Grima, Reuben; Scerri, Eleanor M. L.; Stewart, Mathew; Vella, Nicholas C. (Frontiers in Earth Science, 2022)
The small size and relatively challenging environmental conditions of the semi-isolated Maltese archipelago mean that the area offers an important case study of societal change and human-environment interactions. Following an initial phase of Neolithic settlement, the ‘Temple Period’ in Malta began ~5.8 thousand years ago (ka), and came to a seemingly abrupt end ~4.3 ka, and was followed by Bronze Age societies with radically different material culture. Various ideas concerning the reasons for the end of the Temple Period have been expressed. These range from climate change, to invasion, to social conflict resulting from the development of a powerful ‘priesthood’. Here, we explore the idea that the end of the Temple Period relates to the 4.2 ka event. The 4.2 ka event has been linked with several examples of significant societal change around the Mediterranean, such as the end of the Old Kingdom in Egypt, yet its character and relevance have been debated. The Maltese example offers a fascinating case study for understanding issues such as chronological uncertainty, disentangling cause and effect when several different processes are involved, and the role of abrupt environmental change in impacting human societies. Ultimately, it is suggested that the 4.2 ka event may have played a role in the end of the Temple Period, but that other factors seemingly played a large, and possibly predominant, role. As well as our chronological modelling indicating the decline of Temple Period society in the centuries before the 4.2 ka event, we highlight the possible significance of other factors such as a plague epidemic.